(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: The study described the routine hand hygiene of healthcare workers at Yen Son District Health Center in 2023 and some associated factors. Research method and time: This was a cross-sectional study. There were 246 chances for hand hygiene to be observed using a checklist. The implementation period of the study was from January 2023 to the end of March 2023. Data were analyzed by SPSS software version 16.0. Chi-square and odd ratios were applied with a significant level at 0.05. Results: The prevalence of routine hygiene compliance was 87.8%. The prevalence of routine hygiene compliance was 32% among nurses; the lowest was among midwives (11.1%). There was a relationship between knowledge and healthcare workers’ compliance with routine hand hygiene. This difference was significant with p<0.05. Conclusion: Strengthen training, training and hands-on practice in hand hygiene in departments with low hand hygiene compliance rate. The groups of midwives and midwives with the lowest hand hygiene compliance rate among the groups of titles need to be trained and inspected more often and closely.